A Randomized Clinical Trial Evaluating the Efficacy and Quality of Life of Antibiotic-only Treatment of Acute Uncomplicated Appendicitis: Results of the COMMA Trial. Issue 2 (August 2021) - O'Leary, D. Peter; Walsh, Siun M.; Bolger, Jarlath; Baban, Chwanrow; Humphreys, Hilary; O'Grady, Sorcha; Hegarty, Aisling; Lee, Aoife M.; Sheehan, Mark; Alderson, Jack; Dunne, Ruth; Morrin, Martina M.; et al.
Abstract : Objective: Evaluate the efficacy and quality of life associated with conservative treatment of acute uncomplicated appendicitis. Summary background data: Conservative management with antibiotics only has emerged as a potential treatment option for acute uncomplicated appendicitis. However the reported failure rates are highly variable and there is a paucity of data in relation to quality of life. Methods: Symptomatic patients with radiological evidence of acute, uncomplicated appendicitis were randomized to either intravenous antibiotics only or undergo appendectomy. Results: One hundred eighty-six patients underwent randomization. In the antibiotic-only group, 23 patients (25.3%) experienced a recurrence within 1 year following randomization. There was a significantly better EQ-VAS quality of life score in the surgery group compared with the antibiotic-only group at 3 months (94.3 vs 91.0, P < 0.001) and 12 months postintervention (94.5 vs 90.4, P < 0.001). The EQ-5D-3L quality-of-life score was significantly higher in the surgery group indicating a better quality of life (0.976 vs 0.888, P < 0.001). The accumulated 12-month sickness days was 3.6 days shorter for the antibiotics only group (5.3 vs 8.9 days; P < 0.01). The mean length of stay in both groups was not significantly different (2.3 vs 2.8 days, P = 0.13). The mean total cost in the surgery group was significantly higher than antibiotics only group ([Euro sign]4, 816 vs [Euro sign]3, 077, P < 0.001). Conclusions: Patients with acute, uncomplicated appendicitis treated with antibiotics only experience high recurrence rates and an inferior quality of life. Surgery should remain the mainstay of treatment for this commonly encountered acute surgical condition. Abstract : Supplemental Digital Content is available in the text